Quality and Cost in Community Health Centers. Issue 9 (3rd September 2021) - Carey, Kathleen; Luo, Qian; Dor, Avi
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Quantifying health care quality has long presented a challenge to identifying the relationship between provider level quality and cost. However, growing focus on quality improvement has led to greater interest in organizational performance, prompting payers to collect various indicators of quality that can be combined at the provider level. Objective: To explore the relationship between quality and average cost of medical visits provided in US Community Health Centers (CHCs) using composite measures of quality. Research Design: Using the Uniform Data System collected by the Bureau of Primary Care, we constructed composite measures by combining 9 process and 2 outcome indicators of primary care quality provided in 1331 US CHCs during 2015–2018. We explored different weighting schemes and different combinations of individual quality indicators constructed at the intermediate domain levels of chronic condition control, screening, and medication management. We used generalized linear modeling to regress average cost of a medical visit on composite quality measures, controlling for patient and health center factors. We examined the sensitivity of results to different weighting schemes and to combining individual quality indicators at the overall level compared with the intermediate domain level. Results: Both overall and domain level composites performed well in the estimations. Average cost of a medical visit was negatively associated with quality, although the magnitude of the effect varied across weighting schemes. Conclusion: Efforts toward improvement of primary health care quality delivered in CHCs need not involve greater cost.